Increase of resistance of polystyrene paints when introducing organic-mineral additive - Логанина, Валентина Ивановна; Петухова, Надежда Алексеевна (Eastern-European Journal of Enterprise Technologies, 2013)
The article presents the structure and production technology of organic-mineral additive designed for polystyrene paints as the structuring and dispersant additive, which presents mixed clay with adsorbed surfactant - a reaction product of alkylphenols with ethylene oxide OP-4. It was found that the adsorption of additive OP-4 is 0.00038 g/sm2. The methods for the introduction of organic-mineral additive to formulation of the polystyrene paint were suggested. The polystyrene structure of paint with low content of volatile compounds was designed for exterior and interior building products and designs. The coatings based on the developed polystyrene paint possess increased fracture strength. It was determined that the introduction of organic-mineral additive to the formulation of polystyrene paint provides increase of grinding of paint, reduction of the coverage indicator from 160 to 112 g/m2 , improvement of cohesive strength in 1,6-1,8 times, the modulus of elasticity in 1.2 times, the proportion of the elastic deformation in 2 times and decrease of the proportion of plastic deformation in general deformation of coatings. It was revealed that the polystyrene paints have the best dispensing, and increased by 13% retention capacity. The coatings based on polystyrene paints possess higher quality of form, which is IV-V (coatings based on a reference structure V-VI).